Evaluación de los emprendimientos de la economía popular y solidaria, impulsados por la administración zonal Quitumbe en la ciudad de Quito - García Pérez, Lourdes Estefanía (2015)
The Solidarity Popular Economy in recent decades has been built up, as a set of organizations where the focus is on the welfare of the community, taking into account the primacy of the individual and the social objective over capital, being the main purpose workers access to all means of knowledge and means of production. Based on the principles of the Solidarity Popular Economy initiative and innovation is one of the fundamental pillars of primarily the common good, rather than the individual. Based on these principles the Distrito Metropolitano de Quito by Administración Zonal Quitumbe program has driven the Enterprise of the People's Solidarity Economy are initiatives that promote fair trade, while 33 enterprises have settled divided into two turns business; which are Catering and Crafts, in which the DMQ gives priority those who are least able to find a source of work due to various factors including age, lack of skills, discrimination of race or gender etc. The support provided by the Distrito Metropolitano de Quito by Administración Zonal Quitumbe is organizing participatory fairs in which 33 enterprises have the opportunity to offer their products. Through the research work it was possible to demonstrate that this program has been a great help for entrepreneurs, however the study of new guidelines that will generate an improvement is needed.